Knowledge, Attitudes, and Personal Hygiene Practices among Applied Bachelor Students in Occupational Health and Safety - Suyitno Suyitno (Borneo Scientific Publishing, 2026)
Personal hygiene is an essential component of health promotion, particularly among students in Occupational Health and Safety (OHS) programs who are expected to apply healthy behaviors in academic and practical settings. This study aimed to examine differences in knowledge, attitudes, and personal hygiene practices among OHS D4 students based on individual characteristics. A quantitative observational study with a cross-sectional design was conducted involving 271 OHS D4 students selected through total sampling. Data were collected using a structured self-administered questionnaire assessing respondent characteristics, knowledge, attitudes, and personal hygiene practices. Descriptive analysis and one-way Analysis of Variance (ANOVA) were performed using statistical software with a significance level of p < 0.05. The results indicated that academic level and practical training experience were consistently associated with differences in knowledge, attitudes, and personal hygiene practices, while gender differences were observed only in knowledge. Effect size estimates suggested small to moderate practical significance, indicating meaningful associations rather than mere statistical differences. Although causal inference is limited due to the cross-sectional design and reliance on self-reported data, the findings underscore the importance of early integration of hygiene-focused learning activities and competency-based practical training within OHS curricula to support the development of consistent personal hygiene behaviors among future occupational safety professionals.